Abdominal belts for manual handling in industry: The evidence for and against - R. S. Bridger (AOSIS, 1998)
The paper reviews research on the use of abdominal belts for industrial back injury prevention programmes. The evidence for biomechanical, physiological and psychophysical effects of belt use is presented, following a brief theoretical discussion. Although there is some laboratory evidence that abdominal belts protect the spine when lifting, the findings of field studies are equivocal. Previously injured workers seem to benefit the most both from "back school" training combined with wearing abdominal belts at work. However, far from being the solution to industrial manual handling problems, abdominal belts have only a small part to play in comprehensive risk management programmes aimed at reducing back problems in the workplace.